2006
DOI: 10.1289/ehp.8852
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Relative Bioavailability of Lead in Soil and Soil-Like MaterialsUsing Young Swine

Abstract: In this article we summarize the results of a series of studies that measured the relative bioavailability (RBA) of lead in a variety of soil and soil-like test materials. Reference material (Pb acetate) or Pb-contaminated soils were administered orally to juvenile swine twice a day for 15 days. Blood samples were collected from each animal at multiple times during the course of the study, and samples of liver, kidney, and bone were collected at sacrifice. All samples were analyzed for Pb. We estimated the RBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(171 citation statements)
references
References 8 publications
10
157
1
3
Order By: Relevance
“…Consistent with in situ bioavailability values obtained by Casteel et al (2006), the relative bioaccessibility for the identified inorganic Pb phases in house dust are as follows: Pb on goethite (very high-92% relative to Pb acetate = 100%) [ PbCO 3 (high-73%) [ PbO (medium to high-67%) [ PbSO 4 (low-14%) [ PbCrO 4 (very low-9%). These results along with those from XANES speciation (Table 2) indicate that up to 89% of the total Pb in the composite-36 sample would be highly bioaccessible.…”
Section: Speciation Versus Bioaccessibilitysupporting
confidence: 82%
“…Consistent with in situ bioavailability values obtained by Casteel et al (2006), the relative bioaccessibility for the identified inorganic Pb phases in house dust are as follows: Pb on goethite (very high-92% relative to Pb acetate = 100%) [ PbCO 3 (high-73%) [ PbO (medium to high-67%) [ PbSO 4 (low-14%) [ PbCrO 4 (very low-9%). These results along with those from XANES speciation (Table 2) indicate that up to 89% of the total Pb in the composite-36 sample would be highly bioaccessible.…”
Section: Speciation Versus Bioaccessibilitysupporting
confidence: 82%
“…This question was answered in a recent study of the relative bioavailability (RBA) of lead in blood, liver, kidney, and femur from soil exposures in Joplin, Missouri (located in Jasper County) (Casteel et al 2006). RBA was tested by feeding a precise dose of lead in soil to juvenile swine.…”
Section: Discussionmentioning
confidence: 99%
“…At present, several in vivo animal modelsincluding mouse and swine have beenused to assess Pbrelative bioavailability (RBA, relative to water soluble lead acetate) [11][12][13][14].However, in vivo assays are costly and time consuming, therefore not suitable to measure site-specific Pb-RBA on a large scale. As a result, various in vitro assays to determine Pb bioaccessibility have been developed, whichmeasures the soluble Pb fraction from soil in simulatedhuman gastrointestinalfluids [10][11][15][16].…”
Section: Introductionmentioning
confidence: 99%